PENGARUH KEPEMIMPINAN DAN FINANSIAL INSENTIF TERHADAP MOTIVASI KERJA PADA PT.TELKOM AKSES CABANG BANJARMASIN - Wida Gerhana (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2017)
Abstract,The development of an enterprise in General is affected by the applied leadership in the company. The importance of the role of power employees in organizations which can be utilized as effectively as possible to it, needed ways to drive them to work and use skill or expertise to the maximum. A leader must be able to motivate its employees work and create favorable social conditions for all employees. To improve employee motivation, PT. Telkom Akses financial incentives in the form of giving base salary, allowances, transport allowance meals and allowances.This type of research is research associate, population all employees of PT. Telkom Akses and sample i.e. 40 samples of employees. Research results showed leadership and financial incentives positive effect simultaneously against the influential leadership, work motivation positively and significantly to the motivation of working and financial incentives positive effect against the motivation for work. Should the leader of PT. Telkom Akses noticed the factors of leadership and financial incentives so that it can increas the motivation of working better than ever.